LARANGAN PENGASINGAN TANAH DAN PELUANG INVESTASI ASING DI INDONESIA - FX Sumarja (Fakultas Hukum Universitas Muhammadiyah Yogyakarta, 2014)
Throughout the political history, agrarian law in Indonesia recognize the prohibition of land alienation. Foreigners or foreign legal entities (foreign investors) were banned for land ownership. Argrarian Fundamental Lawsstipulates that foreigners domicile in Indonesia and foreign legal entities which have representatives in Indonesia are only allowed to have land use rights and building lease rights. In practice, foreigners and foreign legalentities prefer to acquire land ownership rights by nominee. Whereas nominee is illegal and has very weak legal position. Article 16 paragraph (1) letter h junto Article 24 Argrarian Fundamental Laws open the opportunitiesfor foreign investors in land tenure through Guna Bangun Serah rights, by positioning the ground as a means of production rather than as an investment. Guna Bangun Serah in Indonesia was marked by the birth of theMinister of Finance of the Republic of Indonesia Decree No. 470 / KMK.01 / 1994 on Procedures for Removal and Utilization of Assets / Country’s Wealth, which adopted the “Turgut’s Formula”, namely the construction and management of dams on the river Syehan Turkey.This study aims to find an alternative land ownership for foreign investors that require land as ingredients, considering the limited tenure in Indonesia to consider theexpediency of justice and legal certainty. The new paradigm is needed in attracting foreign investment in Indonesia, in order to obtain the benefit, justice and legal certainty, through Bangun Guna Serah rights. Article 16 paragraph (1) letter h Argrarian Fundamental Laws stipulates the other rights that are not included: Properties, Cultivation rights, Building rights, Tenure and Rental Rights will be established by law. Bangun Guna Serah rights defined as rights to construct a building and / or its facilities on land that is not his own and then utilize the building and / or its facilities in a certain period of time that has been agreed, as in the future the land, buildings and / or the following facilities will be transfered to the owner of the land after the term expired. Guna Bangun Serah rights can be incorporated into the Land Bill.